2015
DOI: 10.1192/bjp.bp.113.143842
|View full text |Cite
|
Sign up to set email alerts
|

Transference-focused psychotherapy for borderline personality disorder: Change in reflective function

Abstract: Borderline personality disorder is associated with deficits in personality functioning and mentalisation. In a randomised controlled trial 104 people with borderline personality disorder received either transference-focused psychotherapy (TFP) or treatment by experienced community therapists. Among other outcome variables, mentalisation was assessed by means of the Reflective Functioning Scale (RF Scale). Findings revealed only significant improvements in reflective function in the TFP group within 1 year of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 7 publications
9
83
0
8
Order By: Relevance
“…A previous study [9] has demonstrated the efficacy of TFP in the treatment of BPD in a randomized clinical trial, showing a significantly lower drop-out rate and more reduction of borderline symptoms, as well as improvement of psychosocial functioning, personality organization, and reflective functioning compared to experienced community psychotherapy (ECP) [9,10]. The aim of the present study was to assess changes in attachment representations, focusing on narrative coherence and resolution of unresolved attachment in the same dataset.…”
Section: Tablementioning
confidence: 99%
“…A previous study [9] has demonstrated the efficacy of TFP in the treatment of BPD in a randomized clinical trial, showing a significantly lower drop-out rate and more reduction of borderline symptoms, as well as improvement of psychosocial functioning, personality organization, and reflective functioning compared to experienced community psychotherapy (ECP) [9,10]. The aim of the present study was to assess changes in attachment representations, focusing on narrative coherence and resolution of unresolved attachment in the same dataset.…”
Section: Tablementioning
confidence: 99%
“…However, in a review of mechanisms of change in dynamic therapy, it was found that, in five of six studies, change in insight was significantly related to outcome, and in three studies change in defensive On Mechanisms of Change in Psychodynamic Therapy functioning was related to outcome (Crits-Christoph et al 2013). Furthermore, improvement in another important dynamic therapy mechanism measure, namely reflective functioning, has been found to be associated with outcome of dynamic therapy for major depressive disorder (Bressi et al 2017) and borderline personality disorder (De Meulemeester et al 2017;Fischer-Kern et al 2015). Although full mediational analyses documenting change in the mechanism measure (i.e., the mediator) predicting subsequent outcome are rare for any psychotherapy, at least three studies have found that change in a dynamic mechanism measure (insight) predicts subsequent outcome of PDT (Connolly Gibbons et al 2009;Johansson et al 2010;Kallestad et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…6. Other methods not overlapping with outcome may be used to examine mechanisms of change, for example, the self-understanding scale (Connolly Gibbons et al 2009) or the reflective functioning scale (e.g., Fischer-Kern et al 2015). As another approach, treatment-specific interventions may be tested with regard to their relation to outcome (e.g., Barber et al 1996;Crits-Christoph et al 1988).…”
mentioning
confidence: 99%
“…The latter may better be addressed by utilizing interpersonally focused approaches including transference‐focused psychotherapy (TFP; Clarkin, Yeomans, & Kernberg, ; Yeomans, Clarkin, & Kernberg, ) or mentalization‐based therapy (MBT; Bateman & Fonagy, ). In support of this assumption, a study in which patients with BPD were randomly assigned to DBT, TFP, or supportive psychotherapy found that reflective functioning (i.e., mentalization) and attachment security improved only in the TFP group, but not the other two interventions (Levy et al ., ), with similar results being reported in a more recent TFP study (Fischer‐Kern et al ., ). Interestingly, there is no MBT study examining the change of reflective functioning during MBT treatment so far.…”
Section: Introductionmentioning
confidence: 97%